Korupsi Elit Partai Politik di Era Reformasi - Elyta Elyta; Hertanto Hertanto; Tabah Maryanah (Universitas Medan Area, 2022)
This article aims to analyze the corruption committed by party elites in the reform era. The problem is focused on cases of criminal acts of corruption involving a number of Indonesian politicians from 2016 to 2021 with data on various cases of political corruption carried out collaboratively by politicians, bureaucrats, and law enforcement officers. Political corruption is characterized by a state corporatic, because it is initiated by the political elite. In order to approach this problem, the reference to the theory of kleptocracy and political oligarchy as a result of research from Marwing (2021). qualitative. This study concludes that the factor of corruption comes from human greed and waste. Another factor is that it comes from outside the person, because the current corruption is sometimes a factor for coercing the perpetrators because they are bound in a system. Political parties are the dominant entities that influence the emergence of corruption. Because the findings of political corruption state that corruption is carried out to finance political activities, both personally for party cadres, as well as for party political activities.